Comparison between patients rehabilitated with full-arch fixed implant-supported prostheses and complete denture regarding well-being, self-esteem and quality of life - Lopes Piloto, Rafael; de Souza Zimiani, Gabriela; Oliveira e Silva, Cléverson (Brazilian Journal of Implantology and Health Sciences, 2024)
Objective: To evaluate and compare satisfaction and OHRQoL in patients using complete dentures or full-arch fixed implant-supported prostheses. Material and Methods: 200 patients were divided into two groups: 1) Test group (TG): patients rehabilitated with lower full-arch fixed implant-supported prosthesis; and 2) Control group - (CG): patients using complete dentures. Patients had Oral Health-related Quality of Life (OHRQoL) assessed through 4 validated questionnaires: 1) Oral Health Impact Profile (OHIP-14); 2) Rosenberg Self-Esteem Scale (RSS); 3) Orthognathic Quality of Life Questionnaire (OQLQ); and 4) Short Form Health Survey (SF-8). Statistical analysis was done by using the Wilcoxon test, considering a level of significance of 5%. Results: The results demonstrated that the TG presented better results (p<0.001) than the CG in relation to OHIP-14 (9.0±2.36 and 21.0+3.17, respectively), including functional limitation, physical pain, physical and psychological disability, and social and physical disability. Moreover, TG presents better outcomes than CG for RSS (35.0+2.31 and 31.0+2.31, respectively) and OQLQ (16.0+3.19 and 27.5+3.22, respectively), but without difference (p = 0.79) for SF-8 (83.1+6.64 and 83.1+8.16, respectively). Conclusion: Patients with lower full-arch fixed implant-supported prostheses, compared to patients using complete dentures, present a better perception regarding their general well-being, higher self-esteem and quality of life.